Explaining Job Polarization: Routine-Biased Technological Change and Offshoring - Goos, Maarten; Manning, Alan; Salomons, Anna (American Economic Review, 2014)
This paper documents the pervasiveness of job polarization in 16 Western European countries over the period 1993–2010. It then develops and estimates a framework to explain job polarization using routine-biased technological change and offshoring. This model can explain much of both total job polarization and the split into within-industry and between-industry components. (JEL J21, J23, J24, M55, O33)